The Use of Mediation as An Alternative Dispute Resolution In The Settlement of Agrarian Disputes - Sabela Gayo (Syntax Corporation, 2022)
In Indonesia the land dispute is a problem that always arises because it is related to one of the human needs, especially if there is currently an instruction to the settlement efforts of the land mafia in Indonesaia. Usually land cases are always through the court diamana settlement of land cases through judicial channels a lot of shortcomings including very bureaucratic, time consuming labor and quite a lot of costs. Although the principle of dispute resolution in court is resolved with fast time and low cost but in reality it is difficult to implement. One way of Alternative dispute resolution settlement in agrarian dispute settlement is done through appropriate mediation, the management, assessment and handling of land cases which is the task of all levels of society in helping the task of the National Land Agency in resolving land cases can be resolved quickly.